2017
DOI: 10.1108/jefas-02-2017-0047
|View full text |Cite
|
Sign up to set email alerts
|

Dependencia serial de largo plazo en el índice bursátil chileno, a través del coeficiente de Hurst y Hurst ajustado

Abstract: Propósito La presente investigación examina la existencia de memoria de largo plazo por medio del cálculo del coeficiente de Hurst y Hurst ajustado, y del análisis de características de estructuras caóticas en la serie del mercado bursátil de Chile, específicamente a través del Índice de Precios Selectivo de Acciones. Diseño/metodología/enfoque Se desarrolló un breve análisis del mercado, según la metodología de Box y Jenkings. La validez de los resultados se realizó por medio de la prueba propuesta por Broc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…This report complements the previous work of Ikeda (2017), who found that most of the US industrial sector stocks are fractal. The present paper complements that view by using directly stock market prices and online search trends as data sources and uses autoregressive fractional differencing integrated moving average [ARFIMA(p, d, q; P, Q)] processes (Granger and Joyeux, 1980) instead of the Hurst exponent (Hurst, 1951) to approach the fractal nature of the processes involved; so, this paper also provides in the sense of estimation procedures with respect to previous work like Acuña-Opazo and Álvarez-Marín (2017) and Flores-Muñoz et al (2018).…”
Section: Introductionmentioning
confidence: 97%
“…This report complements the previous work of Ikeda (2017), who found that most of the US industrial sector stocks are fractal. The present paper complements that view by using directly stock market prices and online search trends as data sources and uses autoregressive fractional differencing integrated moving average [ARFIMA(p, d, q; P, Q)] processes (Granger and Joyeux, 1980) instead of the Hurst exponent (Hurst, 1951) to approach the fractal nature of the processes involved; so, this paper also provides in the sense of estimation procedures with respect to previous work like Acuña-Opazo and Álvarez-Marín (2017) and Flores-Muñoz et al (2018).…”
Section: Introductionmentioning
confidence: 97%
“…En el caso de las adquisiciones solo se consideran los casos en los cuales se adquiere más del 50% de la participación accionaria.Hechos esenciales o eventos de adquisiciones informados por las empresas que componen el IPSA de la Bolsa de Comercio de Santiago. Período 2001-20181 1 El detalle de esta información está disponible para quien lo requiera en el siguiente enlace: https://www.bolsadesantiago.com/detalle_indice/sp%20ipsa.Fuente: Bolsa de Comercio de Santiago, Superintendencia de Valores y Seguros, Superintendencia de Bancos e Instituciones Financieras.Hechos esenciales o eventos de fusiones informados por las empresas que componen el IPSA de la Bolsa de Comercio de Santiago. Período 2001-20182…”
unclassified